Enlargement of the muscle stem cell pool in linc-MYH-deficient mice does not prevent sarcopenia during aging - Yin, Qing; Labib, Christelle; Boettger, Thomas; Braun, Thomas (Frontiers in Cell and Developmental Biology, 2025)
Loss of skeletal muscle mass and muscle strength during aging (sarcopenia) and reduced skeletal muscle regeneration are often attributed to the age-dependent decline of muscle stem cells (MuSCs). However, it has not been analyzed whether enlargement of the MuSC pool in old animals can attenuate sarcopenia or restore regenerative potential. Here, we directly tested this idea by taking advantage of linc-MYH-mutant mice, which show a substantially increased number of MuSCs in young mice. We found that 24-month-old geriatric linc-MYH knockout mice still maintain a consistently enlarged MuSC pool compared to age-matched controls. MuSCs in geriatric linc-MYH knockout mice were located beneath the basal lamina and remained mostly in a quiescent state. Importantly, enlargement of the MuSC pool did not prevent sarcopenia, or improve muscle function and regeneration. Instead, the larger MuSC pool in geriatric linc-MYH−/− mice resulted in the formation of smaller muscles during regeneration with thicker fibers, characterized by an increased myonuclei content per fiber. Furthermore, we observed shifts of the muscle fiber-type composition in linc-MYH−/− mice during aging, including a reduction of type IIb fibers in the tibialis anterior muscle and a reduction of type IIa fibers in the soleus, combined with an increase of type I fibers.